Liviu Rebreanu - Ion Simuț (Revista de Istorie și Teorie Literară)
The article is a dictionary structured article on Liviu Rebreanu, one of the greatest Romanian prose writers. It presents the biography and works of this writer, a representative one for the literary realism in our culture. It opens with information about the family, the early childhood and education of the writer. Then it offers an outlook on Rebreanu’s debut that remained still unclear in spite of the researches undergone so far, due to the writer’s confessions. After graduating a military college in Budapest, Hungary, and after embracing a military career that lasted less than one and a half year, Liviu Rebreanu decided to resign and end his military life in Hungary and return to his natal country in order to become a Romanian writer. He is 23 years old when he publishes his first short stories in Romanian language (Codrea and Ofilire, published at Sibiu, in 1908). The article points to the literary evolution of the writer, to his journalistic career, to his activity at the Romanian Writers’ Society, and to the way Rebreanu pursued his passion for theatre and his involvement in the Bucharest’s theatrical life of his time. By the end of his life, on September 1st, 1944, Liviu Rebreanu attained status as a writer, became a member of the Romanian Academy and director of theatres. He was no doubt a prominent cultural personality of this epoch. The article presents and analyzes the literary works of Liviu Rebreanu, underlying his prose writer merits in depicting the social milieu. The plays written by Rebreanu, although present on the stage during his life time, are not valuable from the artistic point of view in comparison with his great novels. Liviu Rebreanu brought “the harshness of the realist observation” in the Romanian literature.